الكشف عن مؤشرات مهارات الإدراك البصري ( التمييز البصري ، إدراك العلاقات المكانية ) لدى تلاميذ صعوبات القراءة من وجهة نظر الأخصائيين الأرطفونيين والمعلمين. - معماش, نهاد; سلطاني, الويزة (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة إلى الكشف عن مؤشرات مهارات الإدراك البصري ( التمييز البصري ، إدراك العلاقات المكانية ) لدى تلاميذ صعوبات القراءة . تكونت عينة الدراسة من 30 فردا (أخصائيين أرطفونيين ومعلمين ) تم إختيارهم بطريقة قصدية . ولجمع البيانات تم بناء إستبيان مؤشرات مهارات الإدراك البصري ( التمييز البصري ، إدراك العلاقات المكانية) من طرف الباحثة الذي تكون من 30 بند. إعتمدت الباحثة في هذه الدراسة على المنهج الوصفي، وتم تحليل النتائج عن طريق الحزمة الإحصائية للعلوم الاجتماعية Spss statistics، ولقد أسفرت نتائج الدراسة عن: - وجود مؤشرات مهارة التمييز البصري ومهارة إدراك العلاقات المكانية كصعوبة لدى تلاميذ ذوي صعوبات تعلم القراءة من وجهة نظر الأخصائيين الأرطفونيين والمعلمين بدرجة كبيرة. - عدم وجود فروق ذات دلالة إحصائية بين أراء المعلمين والأخصائيين الأرطفونيين حول مؤشرات مهارتي التمييز البصري و إدراك العلاقات المكانية لدى تلاميذ ذوي صعوبات القراءة في ضوء متغيري الجنس و الخبرة المهنية. This study aimed to reveal indicators of visual perception skills (visual discrimination, perception of spatial relation) among pupils with reading difficulties . The study sample consisted of 30 individuals (speech therapists and teachers) who were chosen intentionally. To collect the data, a questionnaire was built on the indicators of visual perception of skills ( visual discrimination, perception of spatial relation) by the researcher, which consisted of 30 items. In this study, the researcher relied on the descriptive approach, and the results were analyzed by Spss statistics, the results of the study found that: - The presence of indicators of the skill of visual discrimination and the skill of perceiving spatial relations as a difficulty for pupils with reading difficulties from the point of view of specialists and teachers, to a large extent – The are no statistically significant differences between the opinions of teachers and speech therapists about the indicators of visual discrimination skills and of spatial relation among pupils with reading difficulties in the variables of gender and professional experience
Detecting indicators of visual perception skills (visual discrimination, perception of spatial relationship) for students with reading difficulties from the point of view of specialists and teachers.
مقال
Keywords: مؤشرات ، الإدراك البصري ، مهارة التمييز البصري ، مهارة إدراك العلاقات المكانية ، صعوبات القراءة; indicators , visual perception, visual discrimination skill, spatial relation perception skill, reading difficulties.